Apparatchiks and Ideologues in Islamist Turkey - Gürpınar, Doğan. author. aut Link
VIII, 175 p.
Keywords: This book analyzes how AKP’s embedded intellectuals operate as media spin doctors, exploring their transformation from passionately engaged intellectuals into apparatchiks. This project adapts a post-Soviet geography approach to the media, intelligentsia, and political discourse as derivative of authoritarian regimes to the Turkish context. It offers a fresh look at the Turkish political and intellectual scene and a comparative study of the populist-authoritarian politics of Turkey. Situated in the literature on the post-Soviet authoritarian regimes and their ways of governing, as well as their manipulation of public opinion, the book analyzes AKP-aligned intellectuals as apparatchiks. Gürpınar explores the different constellations of pro-AKP intellectuals vindicating the AKP regime from various angles, including: liberal/progressive intellectuals who initially supported the party for its liberal vistas but continued their support by twisting their progressive rhetoric; Islamist intellectuals blending their Islamism with populism; and national security intellectuals who joined after the AKP came to propagate a national security agenda. The book also provides an overview of the mechanisms of political technology, including the media landscape and its running by the AKP, intellectuals themselves as operators of political technology, and the problem of “cultural power.” The book will be of interest to those studying comparative authoritarian politics, populism, political communication, and scholars of Middle East and Eastern Europe. Doğan Gürpınar is an associate professor at Istanbul Technical University (İTÜ). He has published three books in English: Ottoman/Turkish Visions of the Nation, 1860–1950 (2013), Ottoman Imperial Diplomacy (2014), and Conspiracy Nation: Conspiracy Theories in Turkey (2019).